Análisis del sector turístico en el golfo de morrosquillo: estrategias de marketing experiencial para la mejora continua y sostenibilidad (2024)
The present work, carried out by María Jimena Velásquez and Paola de Jesús Orellano Meza, students of the master's degree in Virtual Administration at the Universidad de la Costa, focuses on the analysis of the tourism sector of the Gulf of Morrosquillo, located on the northern coast of the Department. from Sucre. The research addresses various aspects of tourism in this area, highlighting both its benefits and challenges. The methodology used in the study included collaboration with the Inter Hotel in the Municipality of Santiago de Tolú, and was based on the implementation of experiential marketing strategies. Semi-structured interviews and surveys were conducted to obtain detailed qualitative data on tourists' experiences. The main theoretical bases are based on the concepts of experiential marketing, sustainability and customer loyalty. The study was structured around three main axes: • Memorable Experiences: Identify the activities and elements that generate unforgettable experiences for tourists. • Representative Tourist Attractions: Evaluate the most significant tourist attractions that provide significant experiences. • Knowledge Acquired by the Tourist: Analyze the learning and knowledge acquired by tourists during their stay and how this contributes to their overall experience. The importance of keeping tourism sector personnel updated and trained to act as a link between tourists and destinations, facilitating decision-making and promoting loyalty through memorable experiences, was highlighted. In addition, the need for commercial financing to improve tourism offerings and attract new visitors was highlighted. A relevant journalistic note from Semana Magazine highlighted the expansion of the tourist offer in the Department of Sucre, underlining the importance of working to promote new destinations such as Manantiales and trails with extraordinary panoramic views, to boost the regional economy (Semana, 2024). The study's conclusions indicate that tourism in the Gulf of Morrosquillo is fundamental to the local economy, but faces significant challenges that must be addressed to ensure its long-term sustainability. It is recommended to find a balance between economic development, environmental conservation and respect for local cultures.